O impacto da duração da epilepsia em uma série de pacientes com epilepsia do lobo temporal mesial e esclerose hipocampal unilateral - Duarte, Jeana Torres Corso [UNIFESP] (2019)
Hippocampal sclerosis (HS) is the commonest pathology found in patients with epilepsy of temporal lobe onset undergoing corticoamygdalohippocampectomy (CAH) and is present in as many as 80% of these cases (Blümcke et al., 2002; Williamson et al., 1993). However, there is still controversy whether HS is a progressive pathology or not. The purpose of this study was to evaluate if the duration of epilepsy influences MRI volumes of the hippocampus, amygdala, parahippocampal gyrus, entorhinal cortex and temporal pole of both hemispheres, ictal and interictal electroencephalographic patterns and epileptogenic hippocampus neuronal cell density and dentate gyrus granular cells distribution in patients with refractory mesial temporal lobe epilepsy due to hippocampal sclerosis (MTLE/HS). Seventy-seven patients with refractory MTLE/HS submitted to surgery were included. Histopathological analysis included: (1) quantitative: hippocampal subfields and total estimated hippocampal cell density (HCD), thickness of the dentate gyrus – normal, thinning or dispersion; (2) qualitative: type of HS and granule cells pathology in the dentate gyrus (normal, neuronal cell loss, dispersion and bilamination). Ictal and interictal EEG were analysed as follows: 1) Ictal EEG: number of localized, lateralized, non-lateralized, focal to bilateral tonic-clonic seizures and switch of lateralization as well as seizures beginning contralateral to HS were determined; 2) Interictal EEG: interictal epileptiform discharges (IEDs) were considered bilateral when ≥20% of independent IEDs were contralateral to HS. Automated MRI-derived measurements from bilateral temporal structures (hippocampus, amygdala, parahippocampal gyrus, temporal pole, entorhinal cortex) were obtained for 58 subjects. Histopathological and imaging findings were compared with data from specimens obtained in autopsies of age-matched individuals and living controls, respectively, and the data were adjusted for the age at epilepsy onset and the frequency of focal impaired awareness seizures/month. Forty-two (54.5%) patients presented right HS. The greater the duration of epilepsy, the smaller the total estimated HCD (p = 0.025; r = - 0.259). Patients with a normal distribution of the granular cells had a shorter epilepsy duration than those with dispersion (p=0.018) or thinning (p=0.031). There was no relation between electroencephalographic ictal or interictal patterns and epilepsy duration. A reduced ipsilateral hippocampal volume (r = -0.551, p = 0.017) and a smaller hippocampal asymmetry index (r = -0.414, p = 0.002) were correlated to a longer epilepsy duration. The estimated HCD was correlated to the volume of the ipsilateral hippocampus (r=0.420, p=0.001). Our study showed an increasing atrophy of the ipsilateral hippocampus in patients with a longer epilepsy duration. Our data suggest that this reduction in hippocampal volume is related to neuronal loss. Besides that, we also showed an increased probability of exhibiting an abnormal distribution of the granular cells in the dentate gyrus in patients with longer epilepsy duration.